Conversor CA-CC trifásico de estágio único com elevado fator de potência baseado no conversor SEPIC MCD com interruptores bidirecionais - Assunção, Gabriel de Oliveira (2016)
This work presents a new three-phase high power factor single-stage AC-DC converter based on the DCM SEPIC topology, using bidirectional switches. This converter operates as a voltage follower even in open loop (SEPIC DCM converter characteristic), in other words, it emulates a resistance from the electric grid point of view. Therefore, the control effort is reduced to a single control loop to control the DC output voltage, like an output voltage control of a DC-DC converter. This single-stage converter has high reliability, since it employs four active switches with the same command signal and six high frequency diodes for AC-DC conversion with high power factor and high frequency isolation. A system disadvantage is related to the constraint in the choice of transformer turns, which leads to high current values in the secondary-side for lower output voltage specifications. Hereon are presented the operation modes, the ideal waveforms, the main equations of the converter, the numerical simulation results contrasting with the theoretical values and experimental results. Design specifications are 127 V input voltage, 200 V output voltage, 50 kHz switching frequency and 1500 W output power. The prototype is obtained by following the specifications and it shows 0.9981 of power factor, 4.234% of total harmonic distortion and 85.522% of efficiency for rated condition. This converter is considered a choice for low power three-phase systems with low cost realization.